Analisis perbandingan biaya, waktu, dan dampak lingkungan pada pekerjaan lapis pondasi atas menggunakan material recycle dan cut and fill (studi kasus: proyek pembangunan jalur lintas selatan Tulungagung -Trenggalek) - Fahmi Firdaus Alrizal; Diah Listyaningsih; Ihsan Galang Saputra (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2023)
Nowadays, environmental issues in construction project activities that were previously ignored have become major problems as they trigger global warming. Consequently, green construction as a concept of sustainable development has begun to be implemented. It is sort of an effort to minimize the impact of damage to the environment. The construction project of the Tulungagung-Trenggalek southern route carried out material recycling from construction waste to top foundation layer material. The material processing will have an impact on the construction implementation. Therefore, it is necessary to have a study on a comparative analysis of costs, time, and environmental impacts on the work of the top layer using recycled materials and the cut-and-fill method. After using recycled materials, the cost was IDR 2,637,312,551.00, while the cut-and-fill method cost was IDR 2,535,283,401.00. The recycling method took 20 days, whereas the cut-and-fill method took 37 days. Material waste reached 5729.27 tons by the recycle method and 46586.82 tons by the cut-and-fill method. The recycling method caused emissions of 52774.4 kgCO2/liter, while the cut-and-fill method brought in 59935.34 kgCO2/liter. In conclusion, the recycling method can be categorized as a green construction method because it produces fewer emissions and waste than the cut-and-fill method. The recycling method can reduce the impact of environmental damage.